Regulatory and Institutional Drivers of Green Cement Adoption in Indonesia - Ratnawati, Ratnawati; Prasetio, Eko Agus (Journal of Community Based Environmental Engineering and Management, 2026)
The transition toward low-carbon construction materials is essential for achieving decarbonization target, yet adoption of green cement remains limited in many developing countries. This study aims to examine how regulatory and institutional misalignment affects the adoption of green cement in Indonesia’s construction sector. Using a mixed-method approach combining eight in-depth stakeholder interviews, a perception survey of 51 respondents, and regulatory document analysis, the research identifies key structural and institutional barriers influencing adoption. The findings reveal strong coercive pressures on cement producers to decarbonize, contrasted by the absence of mandatory requirements, technical guidelines, and procurement incentives for cement consumers, such as contractors and public project owners. Despite high stakeholder awareness and conditional readiness to adopt green cement, limited trialability, performance validation, and policy alignment constrain diffusion. To address these gaps, the study proposes four integrated interventions: a structured national pilot program, a green public procurement framework, national technical guidelines for green cement application, and ecosystem-wide capacity-building initiatives. The study contributes to sustainability transition and policy adoption literature by highlighting regulatory asymmetry as a central constraint and offers policy-relevant recommendations for accelerating low-carbon construction materials in Indonesia and comparable emerging economies.